2016
DOI: 10.1038/srep23403
|View full text |Cite|
|
Sign up to set email alerts
|

Glucagon-like peptide-1 prevents methylglyoxal-induced apoptosis of beta cells through improving mitochondrial function and suppressing prolonged AMPK activation

Abstract: Accumulation of methylglyoxal (MG) contributes to glucotoxicity and mediates beta cell apoptosis. The molecular mechanism by which GLP-1 protects MG-induced beta cell apoptosis remains unclear. Metformin is a first-line drug for treating type 2 diabetes associated with AMPK activation. However, whether metformin prevents MG-induced beta cell apoptosis is controversial. Here, we explored the signaling pathway involved in the anti-apoptotic effect of GLP-1, and investigated whether metformin had an anti-apoptoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 50 publications
2
26
0
1
Order By: Relevance
“…Previous studies have suggested that activation of GLP‐1 signalling can protect and improve pancreatic β‐cell function against glucotoxicity and lipotoxicity . Given that GLP‐1 is commonly used in the treatment of diabetic hyperglycaemia, we investigated whether liraglutide, a GLP‐1 analogue approved and widely used in the treatment of T2D, protects against high glucose and high FFA‐induced glucolipotoxicity in RINm5f β‐cells.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have suggested that activation of GLP‐1 signalling can protect and improve pancreatic β‐cell function against glucotoxicity and lipotoxicity . Given that GLP‐1 is commonly used in the treatment of diabetic hyperglycaemia, we investigated whether liraglutide, a GLP‐1 analogue approved and widely used in the treatment of T2D, protects against high glucose and high FFA‐induced glucolipotoxicity in RINm5f β‐cells.…”
Section: Resultsmentioning
confidence: 99%
“…MGO can induce the activation of AMPK [33], a known inducer of autophagy [34]. Therefore, we measured AMPK phosphorylation as a possible mechanism underlying the observed effects of MGO on Trx1 and Glo2.…”
Section: Resultsmentioning
confidence: 99%
“…To increase protein glycation, cells were treated with 0.5 mM of MGO, a working concentration widely used in various studies303132. We found that this treatment increased protein glycation without increasing overall cytotoxicity (submitted manuscript).…”
Section: Resultsmentioning
confidence: 91%